Pemanfaatan Agregat Sungai Sewan Kabupaten Sarmi Sebagai Bahan Campuran AC-WC - Marine Mariel Pongturunan; Mary Selintung; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The rapid development of road infrastructure increases the need for materials to be used, including the use of aggregates. This study aims to examine the use of aggregate from the Sewan River in Sarmi Regency as an asphalt mixture. In this study by conducting several tests such as checking the characteristics of course (stone), fine (sand), filler and asphalt characteristics. After that, a mixture of asphalt composition (AC-WC) was made and then the Marshall test was carried out to obtain the properties of the mixture. The results of testing the composition of the AC-WC mixture obtained the composition of the mixture for the optimum asphalt content of 7.50%, coarse aggregate 36.75%, fine aggregate 50.00%, and filler 5.75%. This shows that the aggregate characteristics of the Sewan river for the AC-WC mixture with the conventional Marshall method that meet the 2018 General Specifications of Highways are stability (Asphalt content 4.00%-11.00%), Flow (Asphalt content 4.00%-11 0.00%), VIM (asphalt content 4.00%-7.50%), VMA (asphalt content 5.75%-11.00%) and VFB (asphalt content 5.75%-11.00%). As for the Marshall Immersion test, the remaining Marshall stability value is 95.15%.